Identifikasi Senyawa Fitokimia Kulit Batang Kelor (Moringa oleifera Lamk) Dengan Metode GC-MS dan Uji Toksisitas Terhadap Larva Udang Artemia salina leach - Lay, Antony; Wirawan, I Gede Putu; Wijaya, I Nyoman (Nandur; Vol 2 No 1 (2022), 2022)
Kelor ( Moringa oleifera ) is a plant that grows in tropical climates including Indonesia. All parts of this plant can be used as medicine and other natural products. The purpose of this study was to determine the bioactive compounds contained in moringa stem bark and the level of toxicity expressed by an LC 50 value of less than 1.000 ppm so that it can be used as traditional medicine and other natural products. Identification of bioactive compounds in moringa stem bark using the GC-MS analysis method and toxicity test on Artemia salina Leach shrimp larvae using the Brine Shrimp Lethality Test (BSLT) method. Based on the results of the analysis using GC-MS showed that moringa bark extract contains 14 bioactive compounds. The highest bioactive compounds in the 3 peaks were secondary metabolites in the form of phenols and monoterpenoids. The toxicity test of moringa bark extract against Artemia salina Leach larvae showed that the higher the concentration, the higher the percentage of mortality of Artemia salina Leach, so that the calculated LC 50 value of moringa bark extract was toxic, which was 149,689 ppm.